2021
DOI: 10.1093/mnras/stab367
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of chromospheric molecular hydrogen emission in a solar flare observed by the IRIS satellite

Abstract: We have carried out the first comprehensive investigation of enhanced line emission from molecular hydrogen, H2 at 1333.79 Å, observed at flare ribbons in SOL2014-04-18T13:03. The cool H2 emission is known to be fluorescently excited by Si iv 1402.77 Å UV radiation and provides a unique view of the temperature minimum region (TMR). Strong H2 emission was observed when the Si iv 1402.77 Å emission was bright during the flare impulsive phase and gradual decay phase, but it dimmed during the GOES peak. H2 line br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Significant HXR emissions, produced by non-thermal electrons impacting the lower atmosphere, occur between 12:50 and 13:00 UT, and exhibit multiple bursts with quasi-periodicities between 1 and 2 minutes. Such quasi-periodic pulsations were also observed and studied in EIS, IRIS, and radio spectroscopic observations (Brannon et al 2015;Brosius et al 2016;Karlický et al 2017;Mulay & Fletcher 2021). Five of these bursts are indicated in the figure . Flare energy release is believed to be governed by magnetic reconnection in the corona.…”
Section: Overview Of Observationsmentioning
confidence: 64%
See 1 more Smart Citation
“…Significant HXR emissions, produced by non-thermal electrons impacting the lower atmosphere, occur between 12:50 and 13:00 UT, and exhibit multiple bursts with quasi-periodicities between 1 and 2 minutes. Such quasi-periodic pulsations were also observed and studied in EIS, IRIS, and radio spectroscopic observations (Brannon et al 2015;Brosius et al 2016;Karlický et al 2017;Mulay & Fletcher 2021). Five of these bursts are indicated in the figure . Flare energy release is believed to be governed by magnetic reconnection in the corona.…”
Section: Overview Of Observationsmentioning
confidence: 64%
“…EIS and IRIS observations provide spectroscopic diagnostics of flare plasmas at certain locations across some parts of the flare ribbons. The spectroscopic observations were analyzed by Brannon et al (2015), Brosius & Daw (2015), Brosius et al (2016), andMulay &, revealing quasi-periodic pulsations in the time profiles of the intensity and Doppler-shifted upflows and downflows of the plasma.…”
Section: Overview Of Observationsmentioning
confidence: 99%
“…Our inspection of the spectra did not reveal the presence of any identifiable blends to the line, which is in line with other analyses of this line in flares and active regions (e.g., Polito et al 2016b;Doschek et al 2016;Dudík et al 2017;Jeffrey et al 2018;Young et al 2018, to name a few). Mulay & Fletcher (2021) have shown that H 2 line emission can sometimes be detected at flare ribbons, with the 1402.64 Å line blending the Si IV 1402.77 Å line. To rule out the presence of this blend, we inspected the C II spectral window containing the H 2 1333.48 and 1333.80 Å lines analyzed by Mulay & Fletcher (2021) but did not find any traces of these lines.…”
Section: Spectroscopic Analysis Of the Kernelmentioning
confidence: 99%
“…Mulay & Fletcher (2021) have shown that H 2 line emission can sometimes be detected at flare ribbons, with the 1402.64 Å line blending the Si IV 1402.77 Å line. To rule out the presence of this blend, we inspected the C II spectral window containing the H 2 1333.48 and 1333.80 Å lines analyzed by Mulay & Fletcher (2021) but did not find any traces of these lines. This is likely caused by the relatively shorter exposure time of our observations (1 s) compared to the 8 s exposure time used in the data set they analyzed.…”
Section: Spectroscopic Analysis Of the Kernelmentioning
confidence: 99%
“…Our inspection of the spectra did not reveal the presence of any identifiable blends to the line, which is in line with other analyzes of this line in flares and active regions (e.g., Doschek et al 2016;Polito et al 2016b;Dudík et al 2017;Jeffrey et al 2018;Young et al 2018, to name a few). Mulay & Fletcher (2021) have shown that H 2 line emission can sometimes be detected at flare ribbons, with the 1402.64 Å line blending the Si IV 1402.77 Å line. To rule out the presence of this blend, we inspected the C II spectral window containing the H 2 1333.48 Å and 1333.80 Å lines analyzed by Mulay & Fletcher (2021) but did not find any traces of these lines.…”
Section: Spectroscopic Analysis Of the Kernelmentioning
confidence: 99%